Effect of energy intake on semen characteristics, sex drive, and scrotal circumference of yearling beef bulls - Pruitt, D.; Corah, L.; Kiracofe, G.; McKee, M.; Spire, M. (Kansas State University. Agricultural Experiment Station, 2010)
Simmental and Hereford bulls were fed individually three levels of energy per breed for 200 days beginning shortly after weaning. Then all bulls were adjusted to a roughage ration for 10 days, before grazing brome pasture for 38 days as one group. High energy did not decrease semen quality or sex drive. Energy level affected scrotal circumference of the Simmentals but not Herefords. Weight loss on pasture did not decrease semen quality or sex drive.
Keywords: Beef; Semen; Scrotal circumference; Energy